PENERAPAN GAME EDUKASI DENGAN PENDEKATAN CULTURALLY RESPONSIVE TEACHING UNTUK MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK PADA PEMBELAJARAN IPAS KELAS V SDN BONDONGAN KOTA BOGOR - Intan Julita; Fitri Siti Sundari; Siti Nurjanah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to increase students' learning motivation in science subjects through the application of educational games with a Culturally Responsive Teaching (CRT) approach. The method used is classroom action research (PTK) which is carried out in two cycles, each consisting of four stages. The research subjects were 28 students in class V C at SDN Bondongan. Data was collected through questionnaires and documentation in the form of learning videos and then analyzed using qualitative descriptive techniques. The research results show an increase in students' learning motivation in five aspects of learning motivation in each cycle. In the pre-cycle, the average percentage of five aspects of student learning motivation was 64.98% in the